SEMIOTIC ANALYSIS OF LANGUAGE USE IN MOTIVATIONAL CONTENT ON THE @AFFIRMATION INSTAGRAM ACCOUNT - Fahmi Luqman; Cipto Wardoyo; Dewi Kustanti (Esteem Journal of English Education Study Programme, 2026)
This study investigates the linguistic meanings embedded in motivational content shared on the @affirmations Instagram account by examining both denotative and connotative layers of meaning. Adopting a descriptive qualitative design, the data were collected through document analysis of selected visual posts containing distorted imagery and accompanying textual elements. The findings indicate that the @affirmations account strategically combines unconventional and distorted visual representations with motivational language to critically engage with and subvert the ideology of “toxic positivity” prevalent in digital culture. This interplay between visual distortion and linguistic expression produces a “digital uncanny” effect, which serves to question the societal pressure for constant positivity and perfection in online environments, while simultaneously reframing personal struggles as ironic and reflective social commentary. Unlike previous studies that primarily emphasize persuasive or commercial functions of digital content, this research focuses on the semiotic role of language in constructing meaning within subversive motivational posts. By applying Roland Barthes’ concept of myth, the study extends its analytical scope to the notion of the “digital uncanny,” demonstrating how linguistic and visual elements collaboratively operate to critique ideals of digital perfectionism. This approach contributes to the development of a more nuanced semiotic framework for understanding how language in digital spaces is used to deconstruct dominant social narratives. Consequently, the study offers significant implications for digital media studies, cultural sociology, and semiotics, while also providing practical insights for content creators, digital marketers, educators, and mental health practitioners in interpreting Gen-Z digital culture and evolving perceptions of online well-being.